The Public and Its Problems : An Essay in Political Inquiry - Dewey, John, 1859-1952 (Book collections on Project MUSE., 2012)
"An annotated edition of John Dewey's work of democratic theory, first published in 1927. Includes a substantive introduction and bibliographical essay"--Provided by publisher.